Patterns of injuries and illness among Malaysian athletes during the XVII Asian Games 2014 - Mohamad Shariff A Hamid,; Arshad Puji,; Zaidi Salleh,; Zakiy Jamalullail,; Kamarul Hashimy Hussein, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Although more Malaysians are taking part in International Multisport Games, these athletes well-being at such events have not been fully explored. The purpose of this study was to examine the pattern of injury and illness among Malaysian athletes during the XVII Asian Games 2014. Clinical and socio-demographic information of athletes diagnosed with injury or illness during the centralised training camp and at the Games were recorded in a standardised report form. Throughout the study period, 83 injuries and 64 illnesses were recorded from 276 athletes. Muscle strains and tears were the most common injury followed by ligamentous injury and soft tissues contusion. The number of injuries was highest among badminton players followed by hockey and rugby. Significantly higher incidence of injuries was observed among men than women hockey players. Athletes in individual events had higher proportion of more severe injury than those in team events. Respiratory tract infection was the most frequent illness diagnosed among athletes. Most injuries and illnesses diagnosed among athletes were minor and did not result in time away from participation. The incidence of injuries and illnesses among Malaysian athletes at the XVII Asian Games were comparable with those reported by previous authors. Injury and illness rate were influenced by gender and sports. Fortunately, majority of injuries and illnesses were minor and did not prevent athletes from participation.